Factors responsible for low serum vitamin-D levels in type-2 diabetes mellitus females: a cross-sectional study - Ragav, E. Dinesh; S., Arthi P. (International Journal of Advances in Medicine, 2021)
Background: Diabetes mellitus are a group of disorders as a result of reduced insulin secretion, insulin resistance, and increased glucose production and many more unknown etiologies. As compared to diabetic non-obese, diabetic obese individuals have an increased chance of 13.5 % in developing diabetic complications. Many diabetic patients are found to be vitamin-D deficient and its role in insulin regulation is being studied in many studies. Thus, diabetic complications and vitamin-D deficiency are likely to be developed in obese diabetic females. Methods: Type-2 diabetic females from 30 years to 60 years, attending in medicine as out-patient and female type-2 diabetes patients admitted in medical ward of RRMCH were assessed clinically. Parameters such as anthropometric measurements, weight, height, waist-hip ratio, tested for serum levels vitamin-D including other relevant investigations related to diabetes were done. Totally, 156 patients were assessed. Results: Assessment of 156 patients are as follows, 48.47±9.56years was the mean age of this study group. SD: 5.10±4.36 years is the mean diabetic duration of this study population. 0.98 was the mean waist-hip ratio. 98.93 cm was the mean waist circumference. 24.97 was the mean BMI. Mean fasting blood sugar (FBS) and post-prandial glucose test (PPBS) were: 202.73 mg/dl, 280.99 mg/dl respectively, 9.33% was the mean HbA1C. Majority of the females with type-2 diabetes (92.5%) had low levels of serum vitamin-D. 16.19 ng/ml was the mean serum vitamin-D levels. lower levels of serum vitamin-D were significantly associated with diabetic duration (p=0.082+), poor glycaemic control (p<0.001**) and increased BMI (p=0.011*). Conclusions: Majority of the females with type-2 diabetes mellitus were with waist-hip ratio more than 0.8 and Waist circumference more than 80 cm. Most of the study population had poor diabetic control. Lower levels of serum vitamin-D were found in almost all females with type-2 diabetes mellitus (92.5 %) and the most likely risk factor being obesity and poor glycaemic control as a conclusion of this study.